The politics of English : a Marxist view of language - Holborow, Marnie (Sage, 1999)
The Politics of English offers a major reappraisal of the way in which language is both shaped by, and contributes to, social life. Taking a classical Marxist approach, the author provides a view of the ideological aspects of language.